Ergogenic Effects of Bihemispheric Transcranial Direct Current Stimulation on Fitness: a Randomized Cross-over Trial - Codella, Roberto; Alongi, Rosario; Filipas, Luca; Luzi, Livio (International Journal of Sports Medicine, 2020)
Several types of routines and methods have been experimented to gain neuromuscular advantages, in terms of exercise performance, in athletes and fitness enthusiasts. The aim of the present study was to evaluate the impact of biemispheric transcranial direct current stimulation on physical fitness indicators of healthy, physically active, men. In a randomized, single-blinded, crossover fashion, seventeen subjects (age: 30.9 ± 6.5 years, BMI: 24.8±3.1 kg/m2) underwent either stimulation or sham, prior to: vertical jump, sit & reach, and endurance running tests. Mixed repeated measures anova revealed a large main effect of stimulation for any of the three physical fitness measures. Stimulation determined increases of lower limb power (+ 5%), sit & reach amplitude (+ 9%) and endurance running capacity (+ 12%) with respect to sham condition (0.16<ηp2 < 0.41; p<0.05). Ratings-of-perceived-exertion, recorded at the end of each test session, did not change across all performances. However, in the stimulated-endurance protocol, an average lower rate-of-perceived-exertion at iso-time was inferred. A portable transcranial direct current stimulation headset could be a valuable ergogenic resource for individuals seeking to improve physical fitness in daily life or in athletic training.
Keywords: motor cortex M1; portable brain stimulation; exercise training; tDCS; physical fitness; neuromodulation